Desain dan Implementasi Aplikasi Video Surveillance System Berbasis Web-SIG - Widyantara, I M.O.; Wedanti, N Utami; Swamardika, I B.A. (Majalah Ilmiah Teknologi Elektro, 2015)
Video surveillance system (VSS) is an monitoring system based-on IP-camera. VSS implemented in live streaming and serves to observe and monitor a site remotely. Typically, IP- camera in the VSS has a management software application. However, for ad hoc applications, where the user wants to manage VSS independently, application management software has become ineffective. In the IP-camera installation spread over a large area, an administrator would be difficult to describe the location of the IP-camera. In addition, monitoring an area of IP- Camera will also become more difficult. By looking at some of the flaws in VSS, this paper has proposed a VSS application for easy monitoring of each IP Camera. Applications that have been proposed to integrate the concept of web-based geographical information system with the Google Maps API (Web-GIS). VSS applications built with smart features include maps ip-camera, live streaming of events, information on the info window and marker cluster. Test results showed that the application is able to display all the features built well